Value-sharing and uniqueness of entire functions - Wu, Chun (Український математичний журнал, 2014)
We study the uniqueness of entire functions sharing a nonzero value and obtain some results improving the results obtained by Fang, J. F. Chen, X.Y. Zhang and W. C. Lin, et al.